2011
DOI: 10.1682/jrrd.2010.08.0141
|View full text |Cite
|
Sign up to set email alerts
|

An objective method for selecting command sources for myoelectrically triggered lower-limb neuroprostheses

Abstract: Abstract-Functional electrical stimulation (FES) facilitates ambulatory function after paralysis of persons with spinal cord injury (SCI) by exciting the peripheral motor nerves to activate the muscles of the lower limbs. This study identified a process for selecting command sources for triggering FES with the surface electromyogram (EMG) from muscles partially paralyzed by incomplete SCI, given its high degree of intersubject variability. We found Discriminability Index (DI) to be a good metric to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…FES systems are often used in motor neural prostheses (e.g., the peroneal stimulator for stroke patients (Burridge et al, 2007;Everaert et al, 2013) and may be designed as surface or implantable stimulation systems for control of the arm and hand (Hart et al, 1988;Popović et al, 2004) or for control of standing and walking (Kralj and Bajd, 1989;Nataraj et al, 2012;Dutta et al, 2011;Popović et al, 2003)). FES devices directly assist in the performance of disrupted functions in humans with CNS lesions; furthermore, FES causes changes in cortical excitability and stimulates cortical reorganization (carry-over effects).…”
Section: Introductionmentioning
confidence: 99%
“…FES systems are often used in motor neural prostheses (e.g., the peroneal stimulator for stroke patients (Burridge et al, 2007;Everaert et al, 2013) and may be designed as surface or implantable stimulation systems for control of the arm and hand (Hart et al, 1988;Popović et al, 2004) or for control of standing and walking (Kralj and Bajd, 1989;Nataraj et al, 2012;Dutta et al, 2011;Popović et al, 2003)). FES devices directly assist in the performance of disrupted functions in humans with CNS lesions; furthermore, FES causes changes in cortical excitability and stimulates cortical reorganization (carry-over effects).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated volitonal control of EMG during isometric conditions that reflects muscle force quite well [24]. Specifically, we investigated the impact of anodal tDCS of M1 and cerebellum on two commonly used myoelectric control paradigms for FES control [25], which are initiation/termination of muscle activation, i.e., 'ballistic EMG control ’ for switching FES on-off with a threshold-based classifier [26] and modulation of EMG for 'proportional EMG control’ of FES [27]. The myoelectric visual biofeedback was presented with proportional system dynamics, where the subjects had to modulate the EMG activity (here, EMG is the system input) from one level to another in a finite time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the functional limitations following stroke are varied, including gait dysfunction, fall risk, limited activities of daily living, difficulties in swallowing, reduced upper extremity function, altered communication, besides others. Based on the residual function of a stroke survivor, the number of muscles that can serve as EMG command source [31], the number of muscles that need FES assistance, intensity, frequency, and duration of the EMG-triggered FES-assisted gait training need to be decided. The ability of a stroke survivor to undergo FES-assisted gait therapy also depends on their cardiovascular and neuromuscular capacity besides psychological factors such as motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although both the modalities provide similar orthotic benefit [24,25] where they assist in lifting the foot to clear the ground during stepping action but the relative longterm therapeutic benefit of one modality over the other in facilitating recovery of neurophysiological function has not rigorously been shown. Preliminary research demonstrated the feasibility of EMG control of NMES in partial paralysis as well as its therapeutic benefits [26][27][28][29][30][31]. Dutta et al [31] have shown therapeutic benefits in terms of incremental improvement in the classification of the gait event using a constant EMG-based classifier while the command muscle was undergoing NMES-assisted gait training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation